Productivity measurements, production function and Divisia index numbers - Trivić, Nada (Anali Ekonomskog fakulteta u Subotici, 2025)
Economic efficiency is one of the key economic categories, and the measure of economic efficiency is total productivity. Productivity growth has multiple significance, and above all it is an expression of production efficiency. This paper presents a methodological approach that results in a number of development indicators, and due to its simplicity it has a number of advantages compared to other similar approaches. The concept is based on index numbers of total productivity of all factors. Such an approach involves looking at the net output in relation to the weighted average of the input of all factors. Therefore, a significant part of the work is precisely the input weighting methodology, because it enables appropriate connections of inputs and outputs, but at the same time, combining their different units of measure. The methodology for measuring total factor productivity, presented in this paper, refers to production units, but it is also applicable for the level of the branch, sector, and even the entire economy, as their aggregate size. In accordance with the views of microeconomic theory, the obtained chain two-factor indices were rationalized by Divisia indices. Divisia indexes of prices and quantities of inputs and outputs, as well as technical progress, were presented.